Manufacturing process using CAD/CAM technology / Mohamad Ali Zainol and Mohd Nasir Ab. Manaf - Zainol, Mohamad Ali; Ab. Manaf, Mohd Nasir (1993)
With the advanced in technology in computers, today's manufacturing are made easier. Complicated design are completed at a much faster rate with the availability of such engineering application softwares. Taking full advantage of the available CAD/CAM facilities the authors designed and analysed a two plate mould with two cavities for thermoplastic component. This report on MANUFACTURING PROCESS USING CAD/CAM TECHNOLOGY is divided into 9 chapters. They are:- Chapter 1 - introduces the overview of the project. Chapter 2 - recognises the equipment used and introduction to the application software. Chapter 3 - discusses the mould development, mould study and material used. Chapter 4 - display the mould calculations (manually) and discusses the analysis carried out using Moldflow. Chapter 5 - introduces the proposed mould design. Chapter 6 - discusses the use of I-deas families. Chapter 7 - faces the cost of production. Chapter 8 - discussion of the project and Chapter 9 - is the authors conclusion.